Quantifying crop damage by Grey crowned crane balearica regulorum regulorum and evaluating changes in crane distribution in the North Eastern Cape, South Africa - Van Niekerk, Mark Harry (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 2011)
Complaints of crop damage by cranes on planted maize in the North Eastern Cape, South Africa, have been increasing since the mid-1990's, and in some instances severe losses have been reported. Crop damage by the Grey Crowned Crane Balearica regulorum regulorum near the town of Maclear (31Âº04Â´S 28Âº22Â´E), has been quantified over two growing seasons, and assessed relative to losses caused by foraging Cape Crows Corvus capensis and other feeding damage assumed to be caused by insects. Twelve fields were selected based on previous patterns of crop depredation. Maize seed in seven of the fields was treated with the chemical "—Gaucho' and five fields were planted with untreated maize. In order to determine the source of losses, twenty quadrats (4 m x 4 m) randomly distributed within each field were visited on average every second day, for a period of up to twenty eight days. Results indicate that seed treatments do act as a deterrent to feeding by both cranes and crows, however crane damage is generally insignificant compared to other sources of damage. My study also reviewed past sightings data of the Grey Crowned Crane in an effort to determine if the conversion of former grassland to plantations in this region may have increased foraging activity in maize fields. The data did not allow for clear-cut conclusions regarding changes in distribution or population trends. Conclusions provide direct input into the management of agricultural areas by enabling landowners to take steps to mitigate crop damage. These mitigation measures may either involve the application of seed treatments, or the planting of low risk crops in high risk areas. Future studies should consider the ppossible detrimental effects of chemical seed treatments on crane biology.
Keywords: Cranes (Birds) -- South Africa -- Eastern Cape; Cranes (Birds) -- Geographical distribution -- South Africa -- Eastern Cape; Cranes (Birds) -- Behavior -- South Africa -- Eastern Cape; Cranes (Birds) -- Food -- South Africa -- Eastern Cape; Corn -- Effect of grazing on -- South Africa -- Eastern Cape